INDONESIAN AND MALAYSIAN ISLAMIC EDUCATION CURRICULUM IN SHAPING STUDENT CHARACTER: A Systematic Literature Review of Max Weber's Bureaucracy Theory - Raniya, Pudyas Tataquna; Maknin, Afifah Khurin; Silmi, Thoriq Aji; Lubis, Ardiyansyah; Rusydiyah, Evi Fatimatur; Kusaeri, Kusaeri (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: The lack of character values ​​currently requires education to be more dynamic and adapt to current developments. Purpose: The theory used in this research is based on the concept of character education that integrates moral and ethical values in the learning process. Method: The method applied is Systematic Literature Review (SLR), which involves collecting and analyzing data from various indexed sources, including Google Scholar and Scopus. Result: The results show that the Islamic education curriculum approaches in Indonesia and Malaysia are similar in emphasizing the integration of character values, although there are differences in their implementation. In Indonesia, the curriculum focuses more on the local context and national values, while Malaysia adopts a more systematic approach with an emphasis on universal values. Conclusion: The dominant character dimensions in both curricula include spiritual, social and moral values. In addition, the analysis of community trends through Twitter data shows high attention to student character issues, reflecting the community's hope that character education can be more responsive to the social challenges faced by the younger generation.